KINERJA EKONOMI DAN PARIWISATA PASKA KAWASAN EKONOMI KHUSUS (KEK) PARIWISATA MANDALIKA LOMBOK 2014-2023 - Simatupang, Parhimpunan (FEB Universitas Sam Ratulangi Manado, 2024)
This paper aims to analyse the growth of the tourism industry and foreign direct investment in NTB, as well as its impact on NTB's economic growth, ten years after Mandalika was designated as an exclusive economic zone. The author uses a qualitative approach with a literature study method. The data used is secondary data from documents, reports, and scientific research on tourism, FDI and regional economic growth. Based on analysis, since operating as a special economic zone, especially when the Pertamina Mandalika International Circuit was inaugurated in 2021, the need for tourism development projects, FDI and investment realization has experienced an upward trend. Lastly, NTB also has a positive trend in economic growth indicators which can be seen from NTB's GRDP. The author only focuses on collecting data from secondary data without conducting interviews with decision makers and tourism related parties in the Mandalika exclusive economic zone, so that research with other data sources may produce research that has a different point of view from this research. This research presents a brief overview of the analysis of tourism growth, FDI and economic growth as an impact of the development of exclusive economic zones which can provide recommendations for future research directions and economic and tourism decision makers in other regions. Currently, research examining the impact of the establishment of exclusive economic zone in the context of tourism, FDI and economic growth in Indonesia is still considered quite limited, especially for relatively new tourism development areas such as Mandalika. Key Words: Tourism, Foreign Direct Investment, Economic Growth, exclusive economic zone, Mandalika.